PENGEMBANGAN METODE IN SILICO UNTUK KAJIAN KEAMANAN BAHAN TAMBAHAN PANGAN PADA RESEPTOR ADRENERGIK - Mutiara Nirwana, Hana
Food additives may create some interactions with receptors within our body system and could stimulate certain biological effects when these substances enter our body. One of the important receptors in our body is the adrenergic receptor that regulates our cardiovascular, nerves, and respiratory system. The aim of this research was to develop in silico method for safety assessment of certain food additives (flavoring agents, antioxidants, sweetener, preservatives, and food coloring agents) on adrenergic receptors. The structure of food additives samples were built and then the geometry optimization was performed using Gaussian09 software. The interaction study between food additives and ?2 adrenergic receptor was performed by molecular docking and molecular dynamics simulation. The 3D structure of adrenergic receptor was obtained from crystal structure downloaded from Protein Data Bank (PDB ID: 2RH1). The interaction were analyzed and the dissociation constant (Ki) of the sample compounds were then compared with those nadolol, propranolol, and terbutaline as reference compounds. Based on the analysis results, terbutaline has the largest Ki value of 2,502 nM. This value was then used as a threshold value for safety assessment of food additives. From all of food additives used in this study, there were two samples having lower Ki value than terbutaline, i.e. 2- isobutyl-4,5-dimethyloxazole (BTP 1) and cinnamyl cinnamate (BTP 4) with the Ki values of 0.121 and 0.0115 nM, respectively. The method validation was also conducted by comparing these analysis results with the safety statement published by Joint FAO/WHO Expert Committee on Food Additives (JECFA). From this study, it can be concluded that the developed method was able to predict interaction of food additives on adrenergic receptor which reflects the safety aspect with the accuracy of around 83.3%.